HIGHLY EFFICIENT SYNTHESIS OF 2,4-DISUBSTITUTED OXAZOLES THROUGH PALLADIUM/COPPER COMEDIATED DIRECT ARYLATION REACTION - Regalla, Venkata Reddy; Addada, Rama Krishnam Raju; Puli, Venkat Swamy; Saxena, Abhishek S; Chatterjee, Anindita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study is to synthesize 2,4-disubstituted oxazoles through palladium/copper comediated direct arylation reaction. Methods: 2,4-disubstituted oxazoles (3a-i) have been synthesized by the reaction of 4-substituted oxazole with aryl bromide in the presence of KOH , CuI and Pd(PPh3)4 in dimethoxyethane. Titled compounds (3a-i) were obtained in good yields using an expedient two-step synthesis of 2,4-disubstituted oxazoles from commercially available starting materials Results: The structures of the newly synthesized compounds were characterized by Fourier-transform infrared, 1H NMR, 13C NMR, and mass spectral studies. This method can be an efficient method for the synthesis of 2,4-disubstituted oxazoles (3a-i). Conclusion: Pd(PPh3)4 and CuI cocatalytic system direct arylation of 4-aryl/alkyl oxazoles with various aryl bromides has been developed to generate 2,4-disubstituted oxazoles. The high functional group tolerance and the speed of the reaction afford this method appropriate for the combinatorial synthesis of a variety of 2,4-disubstituted oxazoles.